2005
DOI: 10.1073/pnas.0505765102
|View full text |Cite
|
Sign up to set email alerts
|

Task-specific disruption of perceptual learning

Abstract: For more than a century, the process of stabilization has been a central issue in the research of learning and memory. Namely, after a skill or memory is acquired, it must be consolidated before it becomes resistant to disruption by subsequent learning. Although it is clear that there are many cases in which learning can be disrupted, it is unclear when learning something new disrupts what has already been learned. Herein, we provide two answers to this question with the demonstration that perceptual learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
161
8
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(183 citation statements)
references
References 50 publications
(50 reference statements)
13
161
8
1
Order By: Relevance
“…B, The first seven sessions for the ⌬1 h interval. These plots show the two intervals that are comparable to the intervals used in the paper of Seitz et al (2005), who found time-dependent behavioral interference between two Vernier tasks during early learning. A repeated-measures ANOVA on our data [Condition (E 135 , C 135 ) ϫ Session (7) ϫ P1-P2 Interval (⌬0 h, ⌬1 h)] failed to find a significant interaction between Condition and Interval (F (1,8) ϭ 0.330, p ϭ 0.581).…”
Section: Comparison Of Fast Learning Is Shown At the ⌬0 H (A) And ⌬1 supporting
confidence: 74%
See 3 more Smart Citations
“…B, The first seven sessions for the ⌬1 h interval. These plots show the two intervals that are comparable to the intervals used in the paper of Seitz et al (2005), who found time-dependent behavioral interference between two Vernier tasks during early learning. A repeated-measures ANOVA on our data [Condition (E 135 , C 135 ) ϫ Session (7) ϫ P1-P2 Interval (⌬0 h, ⌬1 h)] failed to find a significant interaction between Condition and Interval (F (1,8) ϭ 0.330, p ϭ 0.581).…”
Section: Comparison Of Fast Learning Is Shown At the ⌬0 H (A) And ⌬1 supporting
confidence: 74%
“…Therefore, high-level networks involved in memory storage in two subsequent tasks may overlap or not, based on variables that are difficult to control. Consequently, opposite conclusions in similar studies of behavioral interference are reported (Seitz et al, 2005;Aberg and Herzog, 2010), although Hung and Seitz (2011) suggest an additional explanation involving eye-movement control and procedural divergences.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Various training conditions and subsequent sleep deprivation can interfere with consolidation, and thus the learning of perceptual skills. For example, training on an additional task while the first skill is still being consolidated [4] or repeated within-day training (overtraining) [5] can prevent learning. Investigating the conditions under which perceptual learning does not occur can help us to better understand the mechanisms of consolidation of cortical changes that produce long-term learning.…”
Section: Introductionmentioning
confidence: 99%